Compatibility Among Cucumis Melo Varieties Inodorus ,Conomon,Flexuosus,Momordica & Utilissiumus - Subha Mary Mathew (Department of Olericulture, College of Horticulture, 1984)
The investigation on compatibility among Cucumis melo var. conomon Mak., Cucumis melo var. inodorous Naud., Cucumis melo var. utilissimus Duth. and Full., Cucumis melo var. flexuosus Naud. and Cucumis melo var. momordica Duth. and Full. Was conducted during October-January 1982-1983 and February – May 1983 at the Instructional Farm of College of Horticulture, Kerala Agricultural University, Vellanikkara, Trichur. The five botanical varieties of Cucumis melo were observed crossable among each other. Oriental pickling melon x long melon and snake melon x snap melon were perfectly crossable (CI > 70%). There was significant maternal effect on crossability index. There was good fruit set and seed set at F1 level. The F1 hybrids were found to be intermediate between the parents for discrete fruit character. Inter varietal heterosis was significant for earliness, yield and their components. Combining ability analysis indicated the role of both additive and non-addetive gene action in the expression of nodes to first male and female flowers, days to first female flower, days to first fruit harvest, days to fruit maturity, seeds/fruit and seed yield/fruit. Additive gene action was predominant in nodes to first male and female flowers, female flowers in first ten and 20 nodes, fruit length, fruit girth, fruit weight, fruit volume, flesh thickness, seeds/fruit, 100 seed weight, seed yield/fruit, fruits/plant and fruit yield/plant. Reciprocal effect was significant in nodes to first male flower, days to first female flower, days to first fruit harvest and days to fruit maturity. The correlation between gca values and per se performance of the parents was significant for all characters. This showed that per se performance of melon varieties would indicate their relative general combining ability effects. Musk melon and snake melon had the maximum genetic distance of 14.49. Long melon and snap melon were the closest (D2-0.38). In the order of affinity the five melon varieties could be arranged as oriental pickling melon, long melon, snap melon, snake melon and musk melon. Fruits/plant contributed maximum (80%) to total genetic divergence.